Approved budget : 1986 fiscal year (Lagos, Nigeria : Government of the Federal Republic of Nigeria, 1986)
The 1986 national budget speech was given by Major-General Ibrahim Babangida, addressing issues of the country's public expenditure; general structural adjustment of the entire economy; dependence on the oil sector and; on imported goods and services.
Includes appendices.
ne 10/08/2021
Loans
Keywords: Budget; Nigeria